The practice of social research - Babbie, Earl R. (Wadsworth Pub. Co., 1998)
Covers all the major methods of social research. By emphasizing an understanding of the theoretical logic behind the research process and demonstrating preferred techniques, the text helps students see methods as a way of thinking and gathering evidence.